2021
DOI: 10.35774/jee2021.04.648
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization Paradigm of Ukrainian Financial Market

Abstract: The article examines the key concepts and theories of modern digitalization paradigm of global financial market, its equilibrium, conditions of financial centres, e-commerce, and FinTech companies. It identifies positive and negative aspects of financial market digitalization and its transformation in global digitalization. Effective principles for the digitalization of Ukraine’s economy are explored. The key ways of financial market digitalization are outlined. The article presents a framework of indicators f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Similar conclusions were obtained by Zhou et al (2021), who, after examining the listed banks in China during 2007-2019, concluded that digitalization does not directly improve the performance of existing companies, while banking and non-banking institutions benefit by reducing inertia. Khamidov et al (2021) built a hierarchical model of FinTech sectors in Ukraine based on indicators such as general indicators of online financial activity of the population, indicators of online and offline accumulation of funds, and indicators of credit activity. It is determined that the most promising areas of financial activity include payment instruments, analysis of financial assets, marketplaces, and neobanking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar conclusions were obtained by Zhou et al (2021), who, after examining the listed banks in China during 2007-2019, concluded that digitalization does not directly improve the performance of existing companies, while banking and non-banking institutions benefit by reducing inertia. Khamidov et al (2021) built a hierarchical model of FinTech sectors in Ukraine based on indicators such as general indicators of online financial activity of the population, indicators of online and offline accumulation of funds, and indicators of credit activity. It is determined that the most promising areas of financial activity include payment instruments, analysis of financial assets, marketplaces, and neobanking.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Obidjon khamidov, Abdukhakim mamanazarov and Volodymyr kulishov (2021) [3] They attempt to give a paradigm of indications for the digitalization of Ukraine's financial market in their essay, which recognizes both positive and negative elements of the country's financial markets going digital.…”
Section: Review Of Literaturementioning
confidence: 99%